A comparison of the CNS effects of enprofylline and theophylline in healthy subjects assessed by performance testing and subjective measures - Tiplady, B; Fagan, D; Lamont, M; Brockway, M; Scott, DB (British journal of clinical pharmacology, 1990)
1. The effects of intravenous infusions of enprofylline, theophylline, and placebo on subjective ratings and on psychological test performance were studied in a double‐blind crossover experiment in 12 healthy subjects who abstained from caffeine throughout the experimental procedures. 2. Mean plasma concentrations of enprofylline were: mean 2.9 mg l‐1 (range 1.9‐3.4). Those for theophylline were: mean 12.1 mg l‐ 1 (range 9.0‐14.4). 3. Performance on the auditory vigilance task showed a significant improvement with theophylline compared with both enprofylline and placebo. The correct detection rates (out of 90) were 50.3, 43.4 and 39.1 respectively. A similar effect was seen with finger tapping rates: 404, 394 and 390 taps min‐1 respectively. Other measures showed no significant effects, although choice reaction time showed a trend towards faster responses with theophylline. 4. Subjective ratings showed that subjects were significantly more alert with theophylline than with enprofylline. Subjects reported themselves as significantly more dizzy and ill with both active drugs compared with placebo. 5. These results suggest that emprofylline largely lacks the CNS stimulant effects of theophylline, but that the incidence of other unwanted effects of the drugs may be similar.